Constructing Scale of Social Dynamics for Kindergarten Children (Journal of the College of Basic Education, 2026)
The current research aimed to construct a pictorial scale of social dynamics for kindergarten children (preparatory stage) aged 5–6 years. To achieve the research objective, the researcher selected a sample of 200 children (boys and girls) from public kindergartens affiliated with the First Al-Rusafa Education Directorate in Baghdad. The researcher developed the research tool (the Pictorial Scale of Social Dynamics) and adopted the Social Change Theory by Auguste Comte (2021) as a theoretical framework for constructing the scale, Upon completing the procedures for building the Social Dynamics Scale, the final version consisted of 36 pictorial items distributed across six domains as follows: Social Interaction with Peers (6 items), Social Communication Skills (6 items), Adaptation to the Social Environment (6 items), Conflict Resolution and Problem-Solving (6 items), Social Initiative and Autonomy (6 items), and Emotional Expression and Social Regulation (6 items). The researcher administered the scale to the research sample, and the time required for completing the test was 15 minutes. The psychometric properties of the scale were verified, and data were analyzed using the Statistical Package for the Social Sciences (SPSS). Thus, the research objective of constructing a pictorial scale of social dynamics for kindergarten children was achieved, and a set of recommendations and suggestions were formulated.